Impact of Regional Income, Unspent Funds, and Balancing Funds on Opportunistic Behaviour of Budget Preparation (Case Study of Regency I City in East Java) - Galang Budi Prayoga (2016)
Budgeting process in local government is quite complex and contain significant political content. Unfortunately, there is some budgeting process that not based on public interest. This behavioral phenomenon in budgeting process may include self-interest and group-interest to allocate budget to their interest. Opportunistic behavior is interesting thing to be examined from the standpoint of agency theory. This study aimed to get empirical evidence of the effect of PAD, SiLP A and Balancing Funds (Dana Perimbangan / DP) on opportunistic behavior in the budgeting process of Regency / City in East Java. The study was conducted in 38 Regency / City in East Java using secondary data time series from the budget of the Regency / City in 2011 to 2014 by using multiple linear regression analysis. Hypothesis testing results shows that the changes in the amount of PAD and DP affect positively to the opportunistic behavior of budgeting process. While SiLP A changes affect insignificantly to the opportunistic behavior of budgeting process. The increase and decrease of opportunistic behavior can be seen from the spread of education, health, infrastructure, grants and social aid. The results could be used as input for local government for improvement in the preparation of the budget. Furthermore, it is advisable for future research in order to add independent variables such as fund transfers and deposits that can not be developed in this study due to lack of data.